Cognitive Enhancement in Neurological and Psychiatric Disorders Using Transcranial Magnetic Stimulation (TMS): A Review of Modalities, Potential Mechanisms and Future Implications - Kim, Tammy D. (Exp Neurobiol, 2019)
Cognitive enhancement refers to the improvement of cognitive function related to deficits that occurred as part of a certain illness. However, the term cognitive enhancement does not yet have a definitive meaning, and its connotations often vary depending on the research of interest. Recently, research interests are growing towards enhancing human cognition beyond what has traditionally been considered necessary using various brain devices. The phenomenon of exceeding the cognitive abilities of individuals who are already functional has also introduced new terminologies as means to classify between cognitive enhancing procedures that are part of treatment versus simply supplementary. Of the many devices used to attain cognitive enhancement, transcranial magnetic stimulation (TMS) is a unique neurostimulatory device that has demonstrated significant improvements in various cognitive domains including memory and cognitive processing skills. While many studies have supported the safety and efficacy of TMS in treatment, there has yet to be an optimization in parameter for TMS that is catered to a certain target group. The current paper aims to review with perspective the many studies that have used TMS for the purpose of cognitive enhancement and provide further insight on the development of an optimal stimulation parameter. The paper reviews 41 peer-reviewed articles that used TMS for cognitive enhancement, summarizes the findings that were apparent for each distinct parameter, and discusses future directions regarding TMS as an elective tool for healthy individuals while considering some of the ethical perspectives that may be warranted.